A Review of Recent Progress on the Anticancer Activity of Heterocyclic Compounds - Negi, Beena; Kwatra, Aarshiya (SynOpen, 2024)
Cancer is one of the most daunting illnesses in the world as compared to many other human diseases. This review article aims to summarize the literature that is already published based on heterocyclic anticancer compounds. Under this broad topic we try to shed a light on anticancer potentiality of oxygen-, sulfur-, and nitrogen-containing heterocyclic compounds, such as quinolines, pyrroles, pyrimidines, pyridines, indoles, also sulfonamides linked heterocycles, benzimidazoles and oxadiazoles.1 Introduction1.1 Drugs in Use for Cancer Treatment1.2 Recently Discovered Anticancer Drugs2 Various Classes of Compounds as Anticancer Agents2.1 Quinoline Derivatives as Anticancer Agents2.2 Benzimidazoles as Anticancer Agents2.3 Indole: A Privileged Scaffold for the Design of Anticancer Agents2.4 Pyrimidine Derivatives as Anticancer Agents2.5 Pyridine Derivatives as Anticancer Agents2.6 Pyrrole Derivatives as Anticancer Agents2.7 Sulfonamides linked with heterocycles as Anticancer Agents2.8 Oxadiazole and Its Derivatives as Anticancer Compounds2.9 Benzothiazole-Triazole Hybrids as Anticancer Compounds3 Conclusion
Keywords: N-heterocycles; benzimidazoles; indoles; sulfonamide; pyrimidines; anticancer drugs